1989
DOI: 10.1007/bf01889214
|View full text |Cite
|
Sign up to set email alerts
|

CT demonstration of the appendix in asymptomatic adults

Abstract: We prospectively examined 103 consecutive adults (67 women, 36 men; mean age: 58.7 years) referred for abdominal and pelvic computed tomography (CT) in whom there was no history of right lower quadrant symptoms or appendectomy. Contiguous 5-mm CT images through the pericecal region were obtained in each subject, once routine scanning was completed. Three radiologists reviewed all CT images and reached a consensus on appendiceal visualization and the quantity of intraperitoneal fat. Statistical methods were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Others have demonstrated that visualization of the appendix is related to intravenous or oral contrast material administration [12], although the use of rectal contrast material may be helpful [22,23]. Decreasing the CT slice thickness and the experience of the radiologist are also beneficial in identifying the appendix [13,24]. In complicated cases, confirmation of the vermiform appendix is usually not possible on a single slice and requires inspection of sequential images through the area of the cecal tip [15,23].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Others have demonstrated that visualization of the appendix is related to intravenous or oral contrast material administration [12], although the use of rectal contrast material may be helpful [22,23]. Decreasing the CT slice thickness and the experience of the radiologist are also beneficial in identifying the appendix [13,24]. In complicated cases, confirmation of the vermiform appendix is usually not possible on a single slice and requires inspection of sequential images through the area of the cecal tip [15,23].…”
Section: Discussionmentioning
confidence: 97%
“…Positive identification of the appendix required demonstration of a tubular, linear, or curved structure, with or without a lumen, which arises from the cecal caput. It had to be unequivocally separable from the cecum and adjacent to the small bowel and had to be conform to the expected location of the appendix [4,13].…”
Section: Ct Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the widespread use of CT to diagnose appendicitis, few studies exist that have systematically evaluated the normal appendix [4], [31], [32], [33], [34]. CT criteria for normal size and wall thickness were based on data from the ultrasound literature.…”
Section: Introductionmentioning
confidence: 99%
“…13 Sonographic criteria for the diagnosis of acute appendicitis included sonographic localization of the appendix at the point of maximal tenderness, an outer diameter of the appendix of greater than 6 mm, noncompressibility of the appendix, and an echogenic periappendiceal inflammatory fat change. The appendix was evaluated for maximal cross-sectional diameter by measurement of the distance between the outer walls and muscle thickness with electronic calipers.…”
Section: Methodsmentioning
confidence: 99%